Does it matter who takes responsibility? The distribution of responsibility for unemployment insurance, employment protection and active labour market policy in five European countries - de Beer, Paul; Schils, Trudie (Amsterdam, 2007)
"In the debate on the relation between social security and the labour market, the focus is on retrenchment of the government to improve the market mechanism. Little attention is being paid to the role of intermediate organisations, in particular trade unions and employers’ organisations (the so-called social partners). Are these institutions just as much an impediment to the market mechanism as the government is often considered to be? Will the social partners, when they are involved in the legislation or administration of social security, pursue their particular (group) interests at the expense of the community? Or can they constitute an efficient mechanism to reconcile conflicting interests of different social groups, or provide the means to highlight the concerns and interests of weaker market actors? The aim of our paper is to gain more insight into the pros and cons of the various options for distributing responsibility between the government, market actors (private companies) and intermediary organisations, especially in the field of unemployment protection (i.e. unemployment insurance, employment protection and active labour market policies). Using cross-national information from Belgium, Denmark, Germany, the Netherlands and the United Kingdom we show to what extent different institutional arrangements of unemployment protection lead to different labour market outcomes. Although the government plays a dominant role in all five countries, there is still a lot of variation in the role of social partners and market actors with respect to unemployment protection. Both first and second order effects of alternative distributions of responsibility are analysed. First order effects include insurance policies, coverage rates, and replacement rates. Second order effects include expenditures on unemployment protection, unemployment rates, flows between employment and unemployment, and the resulting gap between insiders and outsiders. We conclude that there is no systematic relationship between the distribution of responsibility for unemployment insurance, employment protection and active labour market policies on the one hand, and the outcomes in terms of benefit entitlements for various groups and labour market flows on the other hand. The two countries in which trade unions play an important role in the administration of unemployment insurance, viz. Belgium and Denmark, do not stand out with respect to benefit generosity or labour market performance compared to the other three countries."